ANALISIS KINERJA RUAS RUAS JALAN UTAMA DI SEKITAR BANDAR UDARA MUTIARA PALU (Studi kasus: Jl. Abd. Rahman Saleh, Jl. Basuki Rahmat, Jl. Dewi Sartika, Jl. Muh. Yamin) - Tahir, Anas (Jurnal REKAYASA dan MANAJEMEN TRANSPORTASI, 2011)
The increasing number of passengers, goods and aircraft traffic flow in each year in Palu MutiaraAirport will have an impact on the performance of the existing road network around its.Movement of traffic from Mutiara airport or to Mutiara airport, will also be a tendancy toincrease, and can overload the road network around the airport.This study aims to determine the network performance of major roads around the Mutiara airportdue to the operation of the airport, especially at peak hours. Research analysis was conductedusing Indosesian Highway Capasity Manual (IHCM-1997).The results of this study indicated that the performance segment of the main roads aroundMutiara airport is still in stable flow conditions and not under conditions of traffic jams. Degree ofSaturation (DS) on each road segment Abdul Rahman Saleh, Dewi Sartika, Basuki Rahmat andMuh.Yamin respectively was 0.14: 0.46: 0.37 and 0.63, with the highest level of service road AbdulRahman Saleh is the way to the level of service A.